Survey on connectivity and cloud computing technologies: State-of-the-art applied to Agriculture 4.0 - Simionato, Rafael; Torres Neto, José; Santos, Carla; Ribeiro, Bruno; Araújo, Fernando Cesar; Paula, Antonio; Oliveira, Pedro Augusto; Fernandes, Paulo; Yi, Jin (Revista Ciência Agronômica, 2021)
In recent years, agriculture has faced many challenges, from a growing global population to be fed, the work power evasion in the sector, to sustainability requirements and environmental constraints. To satisfy the increasingly demanding stakeholders, the agricultural sector has looked for new ways to tackle these issues. In this context, Information and Communications Technologies (ICTs) have been applied to help the agricultural sector overcome these challenges. This article investigates how two ICTs - connectivity and cloud computing - can leverage and traverse other ICTs, such as Internet of Things and artificial intelligence, enabling the entire productive sector to be supported by decision-making systems, which in turn are based on data-driven models. Moreover, a successful case study on how cloud computing has helped one of SiDi’s biggest customers - a global company - improve its operational performance by obtaining insights from its data is presented.